Γνώσεις στάσεις και πεποιθήσεις των νοσηλευτών σχετικά με τη δωρεά οργάνων και ιστών - Αντωνίου, Αριστόδημος (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: the undeniable development in transplant techniques is not relative to the organ and issues offer of potential donors, resulting to the lack of available organs for transplant. The nurses play a significant role to explanation and clarification of the concept of brain death, to the identification of possible organ donors as well as to the proper approach for the family consent. Thus, the nurses’ participation to this specific process puts them in the crucial position as to their role for the increase of organ donation. Therefore, they must be sufficiently prepared and positively predisposed towards organ donation and transplant. Aim of this research: the major issue of organ donation confuses the entire health community. The present research has as an aim to observe the different views among the nurses as well as their attitude towards the subject in matter. References and Methods: Published research studies and scientific articles were used for this assignment. We used published research studies and recent scientific articles. The search was made in the electronic database PUBMED, MEDLINE, CINAHL, EMBASE and SCOPUS. Results: through the bibliographical review, it was made obvious that a large percentage of the nurses is not sufficiently informed and familiarized with the sense of brain death, transplant and organ donation and therefore have cautious or even negative standpoint towards organ donation. This fact contributes adversely to the attainment of the family consent for organ donation from the relatives of the potential donors. Conclusions: knowledge, attitudes and beliefs of the nurses have an impact on organ donation. The proper preparation of the nurses through educational programs, will contribute to the acquirement of sufficient knowledge as well as to the shaping positive perspective of organ donation.
Keywords: Donation of organs, tissues, etc.; Brain death